2013
DOI: 10.7196/samj.6201
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with contraceptive use in a rural area in Western Cape Province

Abstract: Background. Safe and effective contraceptive use can substantially improve women's reproductive health. Although the contraceptive prevalence rate (CPR) in South Africa is comparable to rates globally, inequalities in CPR affect poor and rural women. This study aimed to determine the CPR and factors associated with contraceptive use in a rural district of Western Cape Province. Method. Cross-sectional survey data based on 412 face-to-face interviews with female participants between 18 and 44 years of age were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 14 publications
4
33
1
Order By: Relevance
“…Partner decision was associated with women’s contraceptive use similar to findings from Ghana, Nigeria and Rwanda where partner approval, partner’s support [39,40] or partner objections [41-43] towards contraceptive choice influenced contraceptive use. In South Africa, women that strongly agreed to male decision making regarding child-bearing did not influence effective contraception [44]. In Uganda [45,46] and Burkina Faso [47], scientific evidence has also shown that positive influence of male partners may affect maternal and child health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Partner decision was associated with women’s contraceptive use similar to findings from Ghana, Nigeria and Rwanda where partner approval, partner’s support [39,40] or partner objections [41-43] towards contraceptive choice influenced contraceptive use. In South Africa, women that strongly agreed to male decision making regarding child-bearing did not influence effective contraception [44]. In Uganda [45,46] and Burkina Faso [47], scientific evidence has also shown that positive influence of male partners may affect maternal and child health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three variables, namely remarriage, paternal education and women’s autonomy were selected for statistical control. The selection of the variables was guided by literature [8, 9, 12, 37, 38]. Some of the variables were however re-classified.…”
Section: Methodsmentioning
confidence: 99%
“…Women who reported no frequency of exposure were grouped as ‘none’, women who accessed at least one of the three outlets less than once a week were grouped as ‘low’ while women who accessed all media outlets more than once a week were grouped as ‘moderate’. Two control variables, namely women autonomy and partner education, were included based on their significance in earlier studies [8, 17, 39]. Women autonomy was derived from responses on women’s participation in three household decisions, namely decisions on own health, purchase of large household items and visit to friends and relatives.…”
Section: Methodsmentioning
confidence: 99%
“…Some of those participants, who reportedly knew about family planning, provided wrong explanations of family planning. Contraceptive use can substantially improve women’s reproductive health (Peer & Morojele 2013). However, because of men’s misconceptions about contraceptives, women might be prevented from accessing contraceptives.…”
Section: Discussionmentioning
confidence: 99%